2009
DOI: 10.3310/hta13150
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose self-monitoring in type 2 diabetes: a randomised controlled trial

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 145 publications
6
110
1
6
Order By: Relevance
“…74,76,78 Twelve of the 18 studies reported measures of variability. 4,49,61,62,69,72,73,74,76,78,80,82 Most (66 %) of these studies showed no statistically significant differences between groups (N=8) 49,61,69,73,74,78,80,82 ; however, studies had limited power due to small numbers of events. Three of the remaining four studies showed significantly less hypoglycemia in the intervention groups, 4,72,76 while one study showed significantly less hypoglycemia in the usual care group.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…74,76,78 Twelve of the 18 studies reported measures of variability. 4,49,61,62,69,72,73,74,76,78,80,82 Most (66 %) of these studies showed no statistically significant differences between groups (N=8) 49,61,69,73,74,78,80,82 ; however, studies had limited power due to small numbers of events. Three of the remaining four studies showed significantly less hypoglycemia in the intervention groups, 4,72,76 while one study showed significantly less hypoglycemia in the usual care group.…”
Section: Safetymentioning
confidence: 99%
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the benefits of SMBG among people with type 2 diabetes who do not use insulin are much less certain. Recent trials, reviews and meta-analyses have shown either no or very small effects of SMBG on glycaemic control 3,4,5 . Given that there is also concern over the high costs associated with SMBG 6 and possible adverse psychological consequences 7,8 , national guidelines state that routine monitoring is no longer recommended for patients who do not use insulin 9,10 , although it may benefit certain groups (eg users of sulponlyureas to reduce risk of hypoglycaemia) 1 .…”
Section: Introductionmentioning
confidence: 99%